PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK KELAS III PADA TEMATIK DI MI HASYIM ASY’ARI - Husna, Riska Latifatul; Masrukin, M. Ali (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
This research is based on students, thematic learning that does not occur reciprocally. For this reason, using Problem Based Learning (PBL) learning can increase students' learning motivation in thematic learning. classroom action research (CAR) was used in this study. Planning (planning), implementation of action (acting), observation (observing) and reflection (reflecting). There are three cycles. Non-test data collection techniques using observation and questionnaires. Questionnaires and observations were used to observe students' responses to learning to apply the Problem Based Learning model, student cooperation, student activity, student conditions and teacher conditions. From the observation of the first cycle, good results were found, the percentage of teacher activity in the first meeting was 77.5%, the teacher's ability to teach was good. Teacher activity in cycle II obtained a percentage of 81% in the very good teaching category. In cycle III the percentage of teacher activity is 91.5%. The teacher's teaching ability from cycles I, II, and III has increased. Cycle I percentage of 61.5% good student activity category. Cycle II percentage of 71% good student activity category. Cycle III the percentage of students' activity abilities is 87.5% with very good student activity categories. The results obtained in learning with the Problem Based Learning (PBL) model in thematic learning in cycles I, II, and III have increased. Student motivation is 52.98 in the low category. In cycle I, the score was 71.87 in the moderate category. There is an increase in learning motivation of 18.89. Cycle II learning motivation score 79.448 indicating moderate level. The third cycle score of 86.85 indicates a high level.